Study of Risk Factors of Stroke in Patients Admitted at Kohalpur Teaching Hospital - Shah, Sanjib Kumar; Shah, Sunil; Shah, Sujeet Kumar; B.K., Shyam (Journal of Nepalgunj Medical College, 2018)
Background: Stroke is the major public health burden and the second major cause of death worldwide. This disease is common in old age persons, however the disease can also be seen in young persons. Identifying the modifiable risk factors of stroke may have contribution in prevention.Objective: The retrospective study was done to study risk factors of stroke in adult patients.Method and Material: This is a hospital based retrospective study conducted in Department of Medicine, Nepalgunj Medical College and st th Teaching Hospital, Kohalpur from the period of 1 January 2015 to 30 October 2016. A total of 119 patients were involved in this study. The diagnosis was confirmed using CT scan after taking history and performing clinical examination. Patients were then evaluated for the presence of both non-modifiable as well as modifiable risk factors. The data analysis was done using SPSS 13.0.Results: The mean age of the patient was 59.76±11.22. Among the collected patients, the higher percentage were male in comparison to female. Ischemic Stroke was more common than hemorrhagic stroke in our study. Other conventional risk factors were as follows: Alcohol use75(63%),cigarette smoking 70(58.8%), hypertension 60 (50.4%),diabetes 11(9.2%),previous vascular event 9(7.6%), heart disease 4(3.4%).Conclusions: Ischemic stroke was more common than hemorrhagic stroke; with alcohol use followed by smoking, hypertension and diabetes mellitus being the most common modifiable risk factors. Incidence of stroke increases with the age and the early recognition and management of the risk factors might reduce this major public burden. JNGMC,  Vol. 14 No. 2 December 2016, Page: 53-55